2019
DOI: 10.1155/2019/2796746
|View full text |Cite
|
Sign up to set email alerts
|

3-Mercaptopropionic, 4-Mercaptobenzoic, and Oleic Acid-Capped CdSe Quantum Dots: Interparticle Distance, Anchoring Groups, and Surface Passivation

Abstract: The optoelectronic properties of quantum dots are strongly controlled by the chemical nature of their surface-passivating ligands. In this work, we present the synthesis, characterization, and surface modification of CdSe quantum dots (QDs) and their application in solar cells. CdSe QDs were capped in oleic acid (OA), 3-mercaptopropionic acid (MPA), and 4-mercaptobenzoic acid (MBA). The QDs were characterized by transmission electron microscopy (TEM), UV-Vis absorption and emission spectrophotometry, thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…PbAc 2 -treated CdSe NC thin films show enhanced PL intensity, as acetate and Pb ions are known to effectively passivate CdSe NCs and increase PL intensity (Figure S9b–d). …”
Section: Resultsmentioning
confidence: 99%
“…PbAc 2 -treated CdSe NC thin films show enhanced PL intensity, as acetate and Pb ions are known to effectively passivate CdSe NCs and increase PL intensity (Figure S9b–d). …”
Section: Resultsmentioning
confidence: 99%
“…The OA ligand is a kind of long-chain ligand that helps with dispersion in a solution, but has the disadvantage of interfering with charge transport between NPL particles [35]. In contrast, as short-chain ligands such as pyridine, 3-mecaptopropionic acid (MPA), and 1,2-ethylenedithiol (EDT) shorten the distance between CdSe NPL particles, they thereby increase interactions with organic material and improve charge transport properties [36,37]. Among these short-chain ligands, we chose to apply pyridine ligand in our experiments due to its good electrical conductivity.…”
Section: Experiments Regarding Cdse Npls Ligand Exchangementioning
confidence: 99%
“…Additionally, the long ligands between 2D structures decrease the charge transfer in optoelectronic devices because of the perovskite nanosheets’ loose packing . Therefore, shorter spacer ligands are more effective in surface passivation while reducing the interlayer distance …”
Section: Introductionmentioning
confidence: 99%
“…33 Therefore, shorter spacer ligands are more effective in surface passivation while reducing the interlayer distance. 34 Recently, 2D perovskite nanoparticles have been used to fabricate high-performance photodetectors. For instance, Li et al 35 have demonstrated that the photoresponsivity of verticaltype photodetectors made of CH 3 NH 3 PbI 3 nanosheets as the active layer is as high as 36 mA W −1 at visible wavelength.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation